Ceng Beng dalam Perspektif Kristen: Menyelaraskan Iman dan Tradisi dalam Budaya Tionghoa - Ante, Defllins; Sutrisno, Sutrisno (Indonesian Journal of Religious, 2024)
This article discusses the relationship between the Ceng Beng practice, a Chinese cultural tradition, and the Christian faith among the Chinese community. Ceng Beng, a festival to honor ancestors through tomb visits and ritual offerings, presents theological challenges for Chinese Christians, as Christianity emphasizes monotheism and worshiping only God. The Chinese Christian community faces a dilemma between preserving ancestral traditions and adhering to Christian teachings. This article identifies three main approaches to responding to Ceng Beng: rejection of the practice, modification of the rituals to align more closely with Christian teachings, and acceptance of the practice in a less ritualistic form. The role of the church and family significantly influences individuals' decisions on whether to follow or modify the Ceng Beng practice. The article also highlights the importance of a pastoral approach that is sensitive to cultural values, as well as the need for the church to provide relevant and contextual theological education. The findings show a diversity of views among Chinese Christians regarding this tradition and emphasize the importance of the church accommodating these differing perspectives with wisdom. Artikel ini membahas hubungan antara praktik Ceng Beng, sebuah tradisi budaya Tionghoa, dengan iman Kristen di kalangan masyarakat Tionghoa. Ceng Beng, yang merupakan hari raya untuk menghormati leluhur melalui ziarah makam dan ritual pemujaan, memiliki tantangan teologis bagi umat Kristen Tionghoa karena ajaran Kristen menekankan monoteisme dan penyembahan hanya kepada Tuhan. Masyarakat Kristen Tionghoa menghadapi dilema antara mempertahankan tradisi leluhur dan mengikuti ajaran Kristen. Artikel ini mengidentifikasi tiga pendekatan utama dalam menanggapi Ceng Beng: penolakan terhadap praktik Ceng Beng, modifikasi praktik agar lebih sesuai dengan ajaran Kristen, dan penerimaan praktik dalam bentuk yang lebih tidak ritualistik. Peran gereja dan keluarga sangat mempengaruhi keputusan individu dalam mengikuti atau mengubah praktik Ceng Beng. Artikel ini juga menekankan pentingnya pendekatan pastoral yang sensitif terhadap budaya, serta perlunya gereja memberikan pendidikan teologis yang relevan dan kontekstual. Hasil penelitian menunjukkan adanya keberagaman pandangan di kalangan umat Kristen Tionghoa dalam menyikapi tradisi ini, dan pentingnya gereja untuk mengakomodasi perbedaan pandangan tersebut dengan bijaksana.